Taxonomic study of the leafhopper genus Singapora (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China with a new species - Lin, Shuanghu; Zhang, Yalin (Zootaxa, 2020)
The genus Singapora Mahmood is reviewed with one new species from China, Singapora shiqianensis sp. nov.. Detailed morphological description, illustration of this new species and a key to all known species (males) from China are provided.